Strategi Meningkatkan Penjualan Pada Usaha Mikro Kecil dan Menengah (UMKM) Melalui TikTok Di Kecamatan Cimanggis Kota Depok - Rizki Plasnajaya; Anugerah Dachi; Nugroho Adi Setyawan; Indra Yoga Pratama; Maysaroh; li Aulia; Susilawati; Siti Khonifah (Jurnal Pengabdian Masyarakat Program Pemberdayaan Masyarakat Nasional, 2024)
TikTok has quickly emerged as a popular social media platform, especially among younger demographics. With its short-form video format and viral trends, TikTok presents a unique opportunity for businesses, including UMKM, to reach a wider audience and engage with customers in a more interactive way. In this section, we will explore the potential benefits of using TikTok as a marketing platform for UMKM in Indonesia and discuss strategies for effectively leveraging this platform to drive growth and success. By harnessing the power of TikTok, UMKM in Indonesia can increase brand awareness, drive traffic to their websites or stores, and ultimately boost sales. The platform's algorithm also allows for content to go viral quickly, providing businesses with the potential to reach millions of users in a short amount of time. With the right approach and creative content, UMKM can truly capitalize on TikTok's popularity and grow their business sustainably in the competitive market